FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN NYERI PUNGGUNG BAWAH PADA TENAGA MEDIS DI SILOAM HOSPITALS LIPPO VILLAGE KARAWACI - Evlyne Erlyana Suryawijaya; Yusak Mangara Tua Siahaan; Ika Paula Fransiska Purba; Vinson Hartoyo (PERDOSNI, 2021)
Introductions: Low back pain (LBP) has been known as one of the most common complaints by healthcare workers (HCWs). LBP in healthcare workers, particularly in Indonesia, is often associated with tentative working schedules, relatively high workload and mechanical factors such as manual handling of the patient. Aim: To investigate the prevalence and factors contributing to LBP in HCWs. Methods: This was an analytic observational study using a cross-sectional method. We gathered primary data using a questionnaire from HCWs in Siloam Hospitals Lippo Village Karawaci, Tangerang, from a period of October to December 2017. Results: A total of 171 subjects were enrolled in this study. We found that the prevalence of LBP in HCWs was 63,7%. Significant factors found to be associated with LBP were occupation as nurse (p=0,007), activity of pulling (p=0,002), lifting (p=0,024), pushing (p= 0,003), and forward bending (p= 0,012). Discussion: LBP in HCWs might be caused by the combination of repetitive trauma and activities which interact with heavyweight and abnormal posture. Keywords: healthcare workers, low back pain.